The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Comparison Of Measures Of Arterial Stiffness Between Women With And Without Polycystic Ovarian Syndrome - Lecher, Madison; Rupp, Kristie; Latchman, Peter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Arterial stiffness; Blood pressure; Body mass index; Etiology; Polycystic ovary; Pulse wave velocity; dept.hms

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Assessing Asymmetry In Collegiate Sprint And Intermediate Hurdlers - Gregory, Robert; Dale, Hunter (Medicine & Science in Sports & Exercise, 2025)
Keywords: Asymmetry; Ground reaction force; Impulse (physics); Jump; Plyometrics; Sprint; dept.hms

Effect Of Creatine Monohydrate Supplementation On VO2 Kinetics In Aerobically Fit Adults - Raymond, Emerson; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Blood lactate; Creatine; Crossover study; Heart rate; Lactate threshold; Percentile; Treadmill; VO2 max; Ventilatory threshold; dept.hms

Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

936 - Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: dept.hms

Reply - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
Keywords: dept.hms

Healthy Futures for Young Women With Obesity: A Mixed Methods Study - Rupp, Kristie; Bryan, JohnM.; Abel-Berei, Catherine (American Journal of Health Promotion, 2025)
Keywords: Focus group; Health promotion; Intervention (counseling); Mental health; Obesity; Perception; Physical activity; Psychological intervention; Psychosocial; dept.hms; health behavior; weight bias; weight stigma; women’s health

Availability of School-Based Sexual and Reproductive Health Services - Zhong, Anthony; Szlosek, Donald; Gao, Chloe; Dang, Nhu; Benes, Sarah (American Journal of Preventive Medicine, 2025)
Keywords: Health services; MEDLINE; Public health; Reproductive health; Sexual behavior; dept.hms

Athletic Training Services Trends Between Public and Private High Schools: A 5-Year Retrospective Analysis - Kim, Donghyeon; Defino, Amir; Eason, Christianne; Casa, Douglas; Yoo, Chaeyeon; Yoshihara, Ayami; Coleman, Kelly; Filep, Erica; Huggins, Robert (Journal of Athletic Training, 2025)
Context Access to athletic trainers (ATs) in high schools is crucial for student-athlete (SA) safety. Although most high schools in the United States have access to athletic training services (ATS), no authors have longitudinally compared ATS trends between public (PUB) and private (PVT) school sectors. Objective To compare ATS trends between PUB and PVT schools from the 2018–2019 through 2022–2023 academic years. Design Longitudinal cross-sectional study. Setting Online survey. Main Outcome Measure(s) High school responses to the Athletic Training Locations and Services survey from all 50 US states and the District of Columbia were queried from the 2018–2019 to 2022–2023 academic years. Average numbers of SAs ( SAs ), sports ( Sports ), full-time ATs ( FtATs ), part-time ATs ( PtATs ), and the sum of full-time and part-time ATs ( ATs ), along with the average weekly contracted hours ( CHrs ) and actual hours ( AHrs ) per school, and ratios of SAs : ATs , Sports : ATs , CHrs : SAs , CHrs : Sports , AHrs : SAs , and AHrs : Sports were examined to track ATS trends over 5 years and compare PUB vs PVT schools. Results Public schools had higher SAs and Sports vs PVT schools (both P < .001). Private schools had higher ATs , CHrs , and AHrs than PUB schools (all P < .050). Ratios of SAs : ATs and Sports : ATs were higher in PUB schools, whereas CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports were higher in PVT schools (all P < .050). From 2018–2019 to 2022–2023, PUB schools increased Sports and Sports : ATs ; PVT schools increased SAs , Sports , ATs , and SAs : ATs (all P < .050). Over the years, PUB schools decreased CHrs : Sports and AHrs : Sports ; PVT decreased CHrs : SAs , AHrs : SAs , CHrs : Sports , and AHrs : Sports . FtATs increased in both sectors, whereas PtATs decreased in only PVT schools. Conclusions Overall, ATS were more extensively provided in PVT schools, based on ATs and ATS hours. Both sectors increased FtATs , which is encouraging. However, as SAs and Sports increased, ATS provided per SA and sport declined.
Keywords: Athletes; Athletic training; Context (archaeology); MEDLINE; Private sector; Training (meteorology); athletes; dept.hms; safety; sports; student health services

Educational Programming to Prevent Violence in Schools in the United States: An Analysis of School Health Profiles - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
This repeated, cross-sectional study examined trends in the availability of school-based programming to prevent violence in middle and high schools across the United States from 2008 to 2020. Overall, violence prevention programming increased in respondent schools throughout the study period. However, important gaps remain, with lingering state-level disparities.
Keywords: Human factors and ergonomics; Injury prevention; Occupational safety and health; Poison control; Respondent; Suicide prevention; adolescent health; dept.hms; health education; school violence prevention; teacher training; youth violence prevention

Position Statements for Advocacy: Does Using Physical Activity as Punishment Make Students Leave Physical Education Wanting to Hide or Seek? - Paulson, Lisa; Knipe, Robert (Strategies, 2025)
This article explains how to use and apply the SHAPE America position statement “Physical Activity Should Not Be Used as Punishment and/or Behavior Management” in one’s own teaching and as an advocacy tool. © 2025 SHAPE America.
Keywords: dept.hms

Adolescent Concern for Body Weight and Engagement in Unhealthy Weight Control Behaviors - McCoy, Stephanie; Bryan, Jessica; Rupp, Kristie (American Journal of Health Promotion, 2025)
Keywords: Binge eating; Body mass index; Body weight; Clinical psychology; Demography; Disordered eating; Eating disorders; Environmental health; Gerontology; Internal medicine; Logistic regression; Medicine; Obesity; Odds; Odds ratio; Pill; dept.hms; eating behaviors; obesity; psychosocial health

Is Your Physical Education Adapted or Adaptive? - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2025)
For decades, adapted physical education advocates have passionately engaged in a debate over two adjectives: adapted vs. adaptive. This article explores the reasons why one is preferred over the other and why it matters, especially to students with disabilities. © 2025 SHAPE America.
Keywords: dept.hms

An Exergames Program for Adolescents With Type 1 Diabetes: Qualitative Study of Acceptability - Mak, Selene S.; Nally, Laura M.; Montoya, Juanita; Marrero, Rebecca; DeJonckheere, Melissa; Joiner, Kevin L.; Nam, Soohyun; Ash, Garrett I. (JMIR Diabetes, 2025)
Background: Numerous barriers to moderate to vigorous physical activity exist for youths with type 1 diabetes (T1D). The virtual exercise games for youth with T1D (ExerT1D) intervention implement synchronous support of moderate to vigorous physical activity including T1D peers and role models. Objective: This study aims to understand the acceptability of this intervention to participants. Methods: We conducted postprogram, semistructured, televideo interviews with participating youths to elicit perspectives on the acceptability of the intervention and experience with the program. Two coders independently reviewed and analyzed each transcript using a coding scheme developed inductively by senior researchers. Discrepancies were resolved by team discussion, and multiple codes were grouped together to produce 4 main thematic areas. Results: All 15 participants provided interviews (aged 14-19 years; 2 nonbinary, 6 females; median hemoglobin A1c level of 7.8% (IQR 7.4%-11.2%), 5 with a hemoglobin A1c level of ≥10%). Qualitative data revealed four themes: (1) motivation to engage in physical activity (PA)—improving their physical capabilities and stabilizing glucose levels were cited as motivation for PA and challenges of living with T1D were cited as PA barriers; (2) experience with and motivation to manage diabetes while engaging in PA—participants provided details of accommodating the inherent uncertainty or limitations of PA with diabetes and sometimes preparing for PA involved psychological and motivational adjustments while some relayed feelings of avoidance; (3) peer support encouraged engagement with the intervention—participants appreciated the peer aspects of components of ExerT1D and participants’ reflections of the facilitated group experience highlight many benefits of a small-group virtual program; and (4) improvements in PA and diabetes self-management efficacy—all participants credited the program with improving or at least raising awareness of T1D management skills. Conclusions: Our virtual PA intervention using an active video game and discussion component provided adolescents with T1D the confidence and peer support to engage in PA, improved awareness of diabetes-specific tasks to prepare for exercise, and improved understanding of the effect of PA on glucose levels. Engaging youths with a virtual video game intervention is a viable approach to overcome barriers to PA for adolescents with T1D. Trial Registration: ClinicalTrials.gov NCT05163912; https://clinicaltrials.gov/ct2/show/NCT05163912
Company: JMIR Diabetes Distributor: JMIR Diabetes Institution: JMIR Diabetes Label: JMIR Diabetes
Keywords: Computer science; Diabetes mellitus; Medicine; Preprint; Psychology; Qualitative research; Sociology; Type 2 diabetes; World Wide Web; dept.hms; peer-reviewed

Moving toward more inclusive, affirming, and health-promoting nutrition education - Benes, Sarah; Burtnyk, Erin (Journal of Physical Education, Recreation & Dance, 2025)
Nutrition units are a staple in many health education courses. While nutrition units can support the acquisition of critical functional knowledge and the development of important skills, there is also the potential for harm and the potential to perpetuate beliefs, ideas, and norms that can lead to disordered eating, the development of unhealthy relationships with food, or shaming of self and others (e.g., fat shaming). The purpose of this article is to outline several factors that may influence how health educators think about and teach nutrition, as well as practical strategies for creating inclusive, affirming, and health-promoting nutrition units.
_eprint: https://doi.org/10.1080/07303084.2025.2455711
Keywords: dept.hms; peer-reviewed

Self perception of leadership styles and behavior in secondary school athletic trainers - Coleman, Kelly; Singe, Stephanie (Internet Journal of Allied Health Sciences and Practice, 2025)

Acute arterial stiffness responses to on-ball kneeling and sitting: Effects of exercise fragmentation and exercise order - Xiao, Yaru; Chen, Wei; Latchman, Peter; Zhou, Zhixiong; Zhu, Weili (European Journal of Applied Physiology, 2025)
Keywords: Arterial stiffness; Ball balance; Blood pressure; Cardio-ankle vascular index; Cardiology; Exercise physiology; Fragmentation; Human physiology; Internal medicine; Kneeling; Medicine; Moderate exercise; Order; Physical exercise; Physical medicine and rehabilitation; Physical therapy; Posture; Sitting; Sports medicine; dept.hms; peer-reviewed

Sex Differences in Response to a 12-Week Resistance Training Exercise Intervention After Cardiac Surgery: A Proof-of-Concept Intervention Trial - Safdar, Basmah; Jarman, Angela; Madsen, Tracy; DeLamielleure, Lauren; Zhou, Bin; Axtell, Robert; Geirsson, Arnar; Mangi, Abeel (Clinical Therapeutics, 2025)
Keywords: Cardiac rehabilitation (CR); Cardiac surgery; Cardiovascular disease (CVD); Intervention (counseling); Medicine; Nursing; Physical therapy; Randomized controlled trial; Resistance strength training; Resistance training; Safety and feasibility; Sex differences; Surgery; dept.hms; peer-reviewed

Trends in school mental health and substance use education - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott E.; Benes, Sarah S. (JAMA, 2025)
The percentage of US youths experiencing mental health and substance use problems has risen rapidly in recent years. Schools are important settings for prevention, but whether preventive programming meets student needs is unknown. This study examined trends in school programming related to mental health and substance use and teacher professional development across US middle and high schools from 2008-2020.
Keywords: dept.hms; peer-reviewed